2022
DOI: 10.1039/d2ta00697a
|View full text |Cite
|
Sign up to set email alerts
|

High cycle stability of Zn anodes boosted by an artificial electronic–ionic mixed conductor coating layer

Abstract: An artificial mixed electronic–ionic conductive coating layer relieves dendrites and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…As is known, water consumption occurs not only during the Zn deposition process (2H 2 O + 2e -→ 2OH -+ H 2 ↑) but also when the battery is at rest [4] . Because Zn is an amphoteric metal, it can react with proton (H + ) (Zn + 2H 2 O → Zn(OH) 2 + H 2 ↑).…”
Section: Free Watermentioning
confidence: 99%
See 2 more Smart Citations
“…As is known, water consumption occurs not only during the Zn deposition process (2H 2 O + 2e -→ 2OH -+ H 2 ↑) but also when the battery is at rest [4] . Because Zn is an amphoteric metal, it can react with proton (H + ) (Zn + 2H 2 O → Zn(OH) 2 + H 2 ↑).…”
Section: Free Watermentioning
confidence: 99%
“…Obviously, both of the two explanations only emphasize the influence of the electrolyte local structure on HER, and it is still unclear which mechanism is in control of water activity. Very recently, Yang et al delved into the origin of HER and suggested that HER primarily originates from solvated water rather than free water [4] . They found that in ZnCl 2 electrolytes, an increase in the ZnCl 2 concentration will promote H 2 evolution.…”
Section: Free Watermentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Many efforts have thus been focused on addressing the Zn-related issues, and however, few signicant breakthroughs have been made in maintaining longterm stability at large current densities. 13,14 Recently, electrolyte engineering is one of the most attractive approaches among the strategies currently proposed to address Zn irreversibility, due to its most maneuverability during battery assembling. The electrolyte additive strategy is regarded as the lowest cost and most effective way in electrolyte engineering.…”
Section: Introductionmentioning
confidence: 99%
“…10–12 Many efforts have thus been focused on addressing the Zn-related issues, and however, few significant breakthroughs have been made in maintaining long-term stability at large current densities. 13,14…”
Section: Introductionmentioning
confidence: 99%